The Determination of Usage Behavior E-wallet DANA as a Payment System Mediated by Trust Factors - Ratu Berlianni Fachira K; Lyla Petra Salsabila; Mardiyani Mardiyani (Cita Konsultindo Research Center, 2024)
This research aims to analyze the influence of the determinants of DANA e-wallet user behavior including perceptions of Service Quality, perceptions of Convenience, and perceptions of the Security System as independent variables. Meanwhile, DANA e-wallet User Behavior is the dependent variable, while DANA e-wallet User Trust is an intervening variable. The population includes students from the Faculty of Economics and Business at Swadaya Gunung Jati University. The sampling technique used was purposive sampling with the criteria of students who had or were currently using the DANA e-wallet and were still active as FEB UGJ students with a sample of 170 respondents using the PLS-SEM technique. The findings show that: user behavior and confidence in using the DANA e-wallet can be positively and significantly influenced by perceived convenience and perceived security system. However, the beliefs and behavior of DANA e-wallet users are not influenced by perceptions of service quality. In order for DANA e-wallet users to increase, DANA e-wallet should increase trust in the behavior of DANA e-wallet users, namely by the company has to improve the quality of DANA e-wallet services by developing innovations such as adding a one-click payment service feature to speed things up. process payments or transfers on the DANA e-wallet.